Performance Evaluation of Co-Axis Counter-Rotation Wind Turbine - Tanate Chaichana (2018)
© 2015 The Authors. Published by Elsevier Ltd. The present work was studied the effect of the tip speed ratio to the starting rotation, rev up rotation, power and torque coefficients of a two-shaft co-axis counter-rotating wind turbine (CR-WT). The prototype of CR-WT was tested in the open type wind tunnel with the velocities of 1.5, 2.0, 3.0, 4.0 and 5.0 m/s. CR-WT consisted of 8 blades. The blade is made of wood. It consists of 2 hubs 2 axis and 4 arms. The inner axis is clockwise rotation and outer axis is anticlockwise rotation. The inner and outer are in the identical axis. Both axes are driven the pulley by using the counter rotating gear. The analysis of the experimental results showed that the cut in wind speed of CR-WT was 1.744 m/s and it is increasing when the tangential force ratio increasing. Rev up rotation period depends on wind speed and tangential force ratio. The average of power coefficient of CR-WT was 14.89%.